Spirits and Exorcism: On the Semiotics of Healing and Recovery - Alter, Joseph S. (Ethos, 2014)
Focusing on the ambiguous and indeterminate relationship between spirit possession and alcoholic spirits, this article shows how biosemiotics provides a way to understand healing and recovery from addiction. The efficacy of treatment for addiction is a spiritual function of social relations anchored in symptomatic diagnosis, rather than in the embodiment of belief as an expression of cultural meaning in ritual forms of treatment. As such, this article offers as critical, semiotic counterpoint to interpretations of ritual efficacy that are based on phenomenology and hermeneutics.